Assessing the impact of mRNA vaccination in chronic inflammatory murine model - Seonghyun Lee; Jisun Lee; Sun-Hee Cho; Gahyun Roh; Hyo-Jung Park; You-Jeung Lee; Ha-Eun Jeon; Yu-Sun Lee; Seo-Hyeon Bae; Sue Bean Youn; Youngran Cho; Ayoung Oh; et al. (npj Vaccines, 2024)
Abstract The implications of administration of mRNA vaccines to individuals with chronic inflammatory diseases, including myocarditis, rheumatoid arthritis (RA), and inflammatory bowel disease (IBD), are unclear. We investigated mRNA vaccine effects in a chronic inflammation mouse model implanted with an LPS pump, focusing on toxicity and immunogenicity. Under chronic inflammation, mRNA vaccines exacerbated cardiac damage and myocarditis, inducing mild heart inflammation with heightened pro-inflammatory cytokine production and inflammatory cell infiltration in the heart. Concurrently, significant muscle damage occurred, with disturbances in mitochondrial fusion and fission factors signaling impaired muscle repair. However, chronic inflammation did not adversely affect muscles at the vaccination site or humoral immune responses; nevertheless, it partially reduced the cell-mediated immune response, particularly T-cell activation. These findings underscore the importance of addressing mRNA vaccine toxicity and immunogenicity in the context of chronic inflammation, ensuring their safe and effective utilization, particularly among vulnerable populations with immune-mediated inflammatory diseases.